การเปลี่ยนแปลงทัศนคติที่มีต่อความตายของจิตอาสาดูแลผู้ป่วยระยะท้ายในโรงพยาบาลกรณีศึกษาโครงการอาสาข้างเตียง The Changing Attitude towards Death of Volunteer Caretakers of Terminally Ill Patients in Hospital: A Case Study of the Bedside Volunteer - กาญจนพิศศาล, สุปรียส์ (Journal of Social Sciences and Humanities Research in Asia, 2017)
This research article has an objective of studying the changing attitude towards death of volunteer caretakers of terminally ill atient in the hospital and reasons that created the changes of this attitude towards death by using research method of phenomenological study by storing information from researched documents, participant observation research and indepth interview with 25 selected volunteer from the Bedside Volunteer project.The result of the study reveals by visiting the terminally ill patient continuously for three months the outcomes were that most of the volunteers had changes in attitude towards death from their previous notion that death is horrifying and is moment of losing own loved ones and also perceiving death as a cause from negligence lifestyle to see it and accept it as a part of life and as an instrument to remind one to live a more quality life without negligence ,there are three main important for these changes ,which are an open minded for learning the reality of life through real experience, listening, contemplating and introspecting of self. However researcher had suggested for further research that there should be studies of changes in attitude towards death of volunteer caretakers of terminally ill patient in the hospital from other project that has a similar function of procedure and also to study the satisfaction of patients and their relatives who had received care from the volunteer. บทคัดย่อ บทความวิจัยนี้มีวัตถุประสงค์เพื่อศึกษาการเปลี่ยนแปลงทัศนคติที่มีต่อความตายของจิตอาสาดูแลผู้ป่วยระยะท้ายในโรงพยาบาลและปัจจัยที่ทำให้เกิดการเปลี่ยนแปลงทัศนคติที่มีต่อความตาย ด้วยวิธีการวิจัยแบบปรากฏการณ์วิทยา โดยทำการเก็บข้อมูลผ่านการวิจัยเอกสาร การสังเกตแบบมีส่วนร่วมและการสัมภาษณ์เชิงลึกจิตอาสาจำนวน 25 คนที่ผ่านการคัดเลือกจากโครงการอาสาข้างเตียง ผลการศึกษา พบว่า การลงเยี่ยมดูแลผู้ป่วยระยะท้ายอย่างต่อเนื่องเป็นระยะเวลา 3 เดือนส่งผลให้จิตอาสาส่วนใหญ่เกิดการเปลี่ยนแปลงทัศนคติที่มีต่อความตาย จากการทัศนคติเดิมที่ว่าความตายเป็นเรื่องน่ากลัวและการพลัดพรากจากสิ่งที่ตนรัก รวมถึงความตายเป็นเรื่องของความประมาทในการใช้ชีวิต กลายเป็นการเปิดใจยอมรับว่าความตายเป็นส่วนหนึ่งของชีวิตและเป็นเครื่องเตือนใจให้ใช้ชีวิตอย่างมีคุณค่าและไม่ประมาท โดยมี 3 ปัจจัยสำคัญที่ทำให้เกิดการเปลี่ยนแปลง คือ การเปิดใจเรียนรู้ความจริงของชีวิตผ่านประสบการณ์ตรง การรับฟังและการทบทวนใคร่ครวญภายในตนเอง ทั้งนี้ ผู้วิจัยได้ให้ข้อเสนอแนะสำหรับการวิจัยในครั้งต่อไป คือ ควรมีการศึกษาการเปลี่ยนแปลงทัศนคติที่มีต่อความตายของจิตอาสาดูแลผู้ป่วยระยะท้ายในโรงพยาบาลจากโครงการอื่นที่มีการดำเนินงานในลักษณะใกล้เคียงกันรวมถึงการศึกษาความพึงพอใจของผู้ป่วยและญาติที่ได้รับการดูแลจากจิตอาสา